Assessing Social Entrepreneurship Initiatives: Journey of Past, Present and Future - Hussain, Nazia Munazer; Ishaq, Muhammad Ishtiaq; Ullah, Abid (Advances in Social Sciences Research Journal, 2014)
Social Entrepreneurship and its role became ubiquitous and should be managed by the organization like other factors to achieve its strategic goals. Being an egalitarian nature, social entrepreneurship is entirely different from another business. Accordingly, this paper delineates the past of organizations, evolution of social entrepreneurship and transformation of generic business operations to social entrepreneurship operations while taking socially networked marketplace into consideration. Through this article, we onslaught an urge where modern organization changed its paradigm to social perspective and act as community based on the principle of collaboration. Based on recent theories, experience and literature, none guidelines will be suggested to design social entrepreneurship dashboard. At the end, guidelines for further academic inquiry, managerial implications and an agenda for future researchers.